Mollusk Diversity in Percut Sei Tuan Silvofishery Ponds, North Sumatra, Indonesia - Ipanna Enggar Susetya; Mohammad Basyuni; Muhammad Rakezza Rifzy Rifzy; Rizka Amelia; Yuntha Bimantara; Rusdi Leidonald; Amanatul Fadhilah (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research